Hubungan sosial antara penganut agama Islam dan agama lain di Aceh, Indonesia - Basri, Hasan (2025)
Aceh is a special province in Indonesia that has the right to implement Islamic sharia. As many as 98.41% of the population adheres to Islam, whereas the rest are minorities, namely Protestant Christians (1.19%), Catholic Christians (0.10%), Buddhists (0.20%) and Hindus (0.10%). There is a claim by the Non-Government Organization (NGO) Setara Institute Jakarta, as well as international and national media, that the Islamic population in Aceh is not tolerant of followers of other religions. This study investigated the form of social relations between adherents of the Islamic faith as the majority population and adherents of other religions as a minority, examined the potential for social conflict between adherents of the Islamic faith and adherents of other religions, and analyzed the role of the Aceh Religious Harmony Forum (FKUB) in helping to realize harmonious social relations among adherents of various religions in Aceh. This qualitative study uses literature, observation, and interviews to collect data. The study used a content analysis method to analyze the data. Social relations are divided into five aspects: religion, economics, education, politics, and culture, focusing on five regions: Banda Aceh, Aceh Singkil, Subulussalam, Southeast Aceh, and Aceh Tamiang. The results show harmonious social relations between Muslim and non-Muslim populations in Aceh. Even though the majority of non-Muslim residents are immigrants, they are comfortable living in Aceh because the government fulfils their social rights. However, several habits of the Christian population, especially in Aceh Singkil and Southeast Aceh, can trigger social conflicts among the population. In dealing with them, the Aceh government collaborates, especially with the existence of the Aceh FKUB. The forum plays a role in achieving harmonious social relations between the Muslim and non-Muslim populations in Aceh. This study refutes the damaging accusations that the Aceh government and followers of Islam are intolerant of followers of other religions.